Policy instruments to limit negative environmental impacts from increased international transport: An economic perspective - Kurt Van Dender; Philippe Crist (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
Transport activities have adverse environmental and health impacts, of which local and regional air pollution, climate change, and noise impacts are the most important. This paper is a non-comprehensive overview of existing and potential policies to deal with these negative impacts, with a focus on international transport. We define international transport as those transport activities that are mainly derived from the globalization of economic activity, not as cross-border transport flows in a more narrow sense. We discuss surface transport, aviation, and maritime transport. The overview is not comprehensive: we focus on climate change, treating other adverse impacts (including aviation noise and local and regional pollution from shipping) more succinctly. This does not reflect a judgment on which impacts are more or less important policy problems, but rather policy interest and the authors' expertise.
Keywords: 330